A Condorcet Voting Theory Based AHP Approach for MCDM Problems - Sweta Bhattacharya; V Raju (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Analytical Hierarchical Process has been used as a useful methodology for multi-criteria decision making environments with substantial applications in recent years. But the weakness of the traditional AHP method lies in the use of subjective judgement based assessment and standardized scale for pairwise comparison matrix creation. The paper proposes a Condorcet Voting Theory based AHP method to solve multi criteria decision making problems where Analytical Hierarchy Process (AHP) is combined with Condorcet theory based preferential voting technique followed by a quantitative ratio method for framing the comparison matrix instead of the standard importance scale in traditional AHP approach. The consistency ratio (CR) is calculated for both the approaches to determine and compare the consistency of both the methods. The results reveal Condorcet – AHP method to be superior generating lower consistency ratio and more accurate ranking of the criterion for solving MCDM problems.